Anti‐inflammatory and anticancer activities of Naringenin‐loaded liquid crystalline nanoparticles in vitro. Issue 1 (29th November 2020) - Wadhwa, Ridhima; Paudel, Keshav Raj; Chin, Li Hian; Hon, Chian Ming; Madheswaran, Thiagarajan; Gupta, Gaurav; Panneerselvam, Jithendra; Lakshmi, Thangavelu; Singh, Sachin Kumar; Gulati, Monica; Dureja, Harish; Hsu, Alan; et al.
Abstract: In this study, we had developed Naringenin‐loaded liquid crystalline nanoparticles (LCNs) and investigated the anti‐inflammatory and anticancer activities of Naringenin‐LCNs against human airway epithelium‐derived basal cells (BCi‐NS1.1) and human lung epithelial carcinoma (A549) cell lines, respectively. The anti‐inflammatory potential of Naringenin‐LCNs evaluated by qPCR revealed a decreased expression of IL‐6, IL‐8, IL‐1β, and TNF‐α in lipopolysaccharide‐induced BCi‐NS1.1 cells. The activity of LCNs was comparable to the positive control drug Fluticasone propionate (10 nM). The anticancer activity was studied by evaluating the antiproliferative (MTT and trypan blue assays), antimigratory (scratch wound healing assay, modified Boyden chamber assay, and immunoblot), and anticolony formation activity in A549 cells. Naringenin LCNs showed promising antiproliferative, antimigratory, and anticolony formation activities in A549 cells, in vitro. Therefore, based on our observations and results, we conclude that Naringenin‐LCNs may be employed as a potential therapy‐based intervention to ameliorate airway inflammation and to inhibit the progression of lung cancer. Practical applications: Naringenin was encapsulated into liquid crystalline nanoparticles, thus, attributing to their sustained‐release nature. In addition, Naringenin‐loaded LCNs efficiently reduced the levels of pro‐inflammatory markers, namely, IL‐1β, IL‐6, TNF‐α, and IL‐8. In addition, the Naringenin‐loaded LCNs also possess potent anticancer activity, when tested in the A549 cell line, as revealed by the inhibition of proliferation and migration of cells. They also attenuated colony formation and induced apoptosis in the A549 cells. The findings from our study could form the basis for future research that may be translated into an in vivo model to validate the possible therapeutic alternative for lung cancer using Naringenin‐loaded LCNs. In addition, the applications of Naringenin‐loaded LCNs as an intervention would be of great interest to biological, formulation and respiratory scientists and clinicians. Abstract : Naringenin was encapsulated into liquid crystalline nanoparticles. Naringenin‐loaded LCNs efficiently reduced the levels of pro‐inflammatory cytokines. Naringenin‐loaded LCNs also possess potent anti‐cancer activity in A549 cell line.